Levels of Mental Health Among Students at Higher Education Institutes - Rosli, Hazlin Falina; Yusuf, Norli; Abdullah, Nur’aina Nabila Dundai; Ismail, Nur Aisyah; Mat Isa, Nur Amilah Fadlina (Jurnal Pendidikan Bitara UPSI, 2024)
The increase in the number of mental disorders among students in HEIs has sparked concern to various quarters in institutions of learning. Mental health problems occur due to various factors including depression, anxiety and extreme stress and eventually lead to suicide. Therefore, issues related to mental health and mental health care are very important to focus on in society. This study was conducted to identify the level of mental health among students in IPT in two IPTS located in the suburbs and rural areas. The results of the Depression Anxiety Stress Scale (DASS) questionnaire found that there were three indicators of stress, anxiety and depression were at normal levels. Yet there is an average student has experienced stress, anxiety and depression at least once in life. This tendency needs to be taken seriously because it can lead to more serious mental health problems. The results of this study are expected to provide recommendations to the relevant parties regarding the level of health of students in IPT and how to solve the problem from the aspect of communication, especially among students.